A pilot study of alternative substrates in the critically Ill subject using a ketogenic feed - McNelly, Angela; Langan, Anne; Bear, Danielle E.; Page, Alexandria; Martin, Tim; Seidu, Fatima; Santos, Filipa; Rooney, Kieron; Liang, Kaifeng; Heales, Simon J.; Baldwin, Tomas; Alldritt, Isabelle; et al. (Nature communications, 2023)
Bioenergetic failure caused by impaired utilisation of glucose and fatty acids contributes to organ dysfunction across multiple tissues in critical illness. Ketone bodies may form an alternative substrate source, but the feasibility and safety of inducing a ketogenic state in physiologically unstable patients is not known. Twenty-nine mechanically ventilated adults with multi-organ failure managed on intensive care units were randomised (Ketogenic n = 14, Control n = 15) into a two-centre pilot open-label trial of ketogenic versus standard enteral feeding. The primary endpoints were assessment of feasibility and safety, recruitment and retention rates and achievement of ketosis and glucose control. Ketogenic feeding was feasible, safe, well tolerated and resulted in ketosis in all patients in the intervention group, with a refusal rate of 4.1% and 82.8% retention. Patients who received ketogenic feeding had fewer hypoglycaemic events (0.0% vs. 1.6%), required less exogenous international units of insulin (0 (Interquartile range 0-16) vs.78 (Interquartile range 0-412) but had slightly more daily episodes of diarrhoea (53.5% vs. 42.9%) over the trial period. Ketogenic feeding was feasible and may be an intervention for addressing bioenergetic failure in critically ill patients. Clinical Trials.gov registration: NCT04101071. Critical illness leads to altered metabolic states and bioenergetic failure caused by impaired utilisation of glucose, fatty acids and amino acids. Here the authors show ketogenic diets may provide a safe and acceptable alternative metabolic fuel enabling energy production and maintaining tissue homeostasis.